2012
DOI: 10.1016/j.jpainsymman.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rural Palliative Care Program in the Calgary Zone of Alberta Health Services

Abstract: Specialized rural models of palliative care are greatly needed to address the challenges rural communities face in providing palliative care services and to ensure that their unique strengths and needs are considered. In late 2005, a Rural Palliative Care Program was developed to support primary care providers in delivering palliative care to patients in rural communities outside of Calgary, Alberta, Canada. The program was grounded in the needs of individual communities, incorporated integral roles for local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…2,11,15 Very few have evaluated and reported the success or otherwise of those models. 16,17 in 2015, Bakitas et al completed a comprehensive review of current practice and the state of research relating to palliative care delivery in rural settings. 10 They concluded that education was extremely valuable and could make a significant difference for low cost.…”
Section: Discussionmentioning
confidence: 99%
“…2,11,15 Very few have evaluated and reported the success or otherwise of those models. 16,17 in 2015, Bakitas et al completed a comprehensive review of current practice and the state of research relating to palliative care delivery in rural settings. 10 They concluded that education was extremely valuable and could make a significant difference for low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Studying rural views of the ‘good death’ is important because these may differ from urban views (Spice et al . ). In addition, ageing is more pronounced in rural areas, and rural areas typically have fewer health and social services as compared to urban areas (Downing & Jack ).…”
Section: Introductionmentioning
confidence: 97%
“…While efforts are made to define 'rural' geographically (based on population density or distance from services), Wilson et al (2009a,b) suggest rural people define themselves as 'rural' and perceive themselves as different from urbanites. Studying rural views of the 'good death' is important because these may differ from urban views (Spice et al 2012). In addition, ageing is more pronounced in rural areas, and rural areas typically have fewer health and social services as compared to urban areas (Downing & Jack 2012).…”
Section: Introductionmentioning
confidence: 99%
“…14,19,24,25 The development of the PPCS as a state-wide service has ensured access to services regardless of where a family is located. More than half (58%) of children referred to the service reside in a regional or rural location.…”
Section: Access To Carementioning
confidence: 99%